The Helicobacter pylori urease virulence factor is required for the induction of hypoxia-induced factor-1α in gastric cells - Valenzuela-Valderrama, Manuel; Cerda-Opazo, Paulina; Backert, Steffen; González, María Fernanda; Carrasco-Véliz, Nicolás; Jorquera-Cordero, Carla; Wehinger, Sergio; Canales, Jimena; Bravo, Denisse; Quest, Andrew F.G. (Cancers, 2019)
Chronic Helicobacter pylori infection increases the risk of gastric cancer and induction of hypoxia-induced factor (HIF), which is frequently associated with the development and progression of several types of cancer. We recently showed that H. pylori activation of the PI3K-AKT-mTOR pathway in gastric cells increased HIF-1α expression. Here, we identified the H. pylori virulence factor responsible for HIF-1α induction. A mutant of the H. pylori 84-183 strain was identified with reduced ability to induce HIF-1α. Coomassie blue staining of extracts from these bacteria separated by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) revealed poor expression of urease subunits that correlated with reduced urease activity. This finding was confirmed in the 26695 strain, where urease mutants were unable to induce HIF-1α expression. Of note, HIF-1α induction was also observed in the presence of the urease inhibitor acetohydroxamic acid at concentrations (of 20 mM) that abrogated urease activity in bacterial culture supernatants, suggesting that enzymatic activity of the urease is not required for HIF-1α induction. Finally, the pre-incubation of the human gastric adenocarcinoma cell line AGS with blocking antibodies against Toll-like receptor-2 (TLR2), but not TLR4, prevented HIF-1α induction. In summary, these results reveal a hitherto unexpected role for the urease protein in HIF-1α induction via TLR2 activation following H. pylori infection of gastric cells.
CRIS-Team Scopus Importer:2019-07-19
Keywords: Helicobacter pylori; HIF-1α; Toll-like receptor 2 (TLR2); Urease